Analisis Laporan Keuangan Untuk Mengukur Kinerja Keuangan Pt. Kimia Farma pada Bursa Efek Indonesia - Tengku Chairrani; Muhammad Arif; Arnida Wahyuni Lubis (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
This research aims to see how the financial performance of PT. Kimia Farma uses liquidity and profitability ratio analysis for the 2017-2021 period, and whether PT. Kimia Farma is experiencing potential bankruptcy based on the Altman Z-Score model for the 2017-2021 period. This research uses quantitative descriptive methods. The type of data used by researchers is quantitative data and qualitative data obtained from www.idx.id. Data collection takes the form of literature study and documentation. Bankruptcy prediction calculations use the Altman Z-Score Model and profitability ratios ROA, ROE, and Net Profit Margin. The research results show that the Liquidity Ratio value of PT. Kimia Farm Ajika is measured by the Current Ratio which is in accordance with industry standards, however the company's quick ratio is still below the industry standard value. Profitability value of PT. Kimia Farma is still below industry standards due to the company's lack of minimizing costs which causes the company's profits to decrease. In calculating bankruptcy using the Altman Z-Score method, the company can be said to be good because it is still above the standard value. There are recommendations that can be used as input for PT. Kimia Farma, Tbk must further increase working capital in order to create and increase profits which will have an impact on the increase in shares and must minimize the company's operational costs.